Baptism as a Consequence: A Historical Study of NZG Evangelism among the Karo People (1890–1941) - Mehamad Wijaya Tarigan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study examines the evangelistic paradigm of the Nederlandsche Zendingsgenootschap (NZG) among the Karo people between 1890 and 1941, arguing that baptism functioned as a consequence rather than the primary goal of mission. Employing a historical-hermeneutical method, this research integrates archival baptismal data, missionary reports, and contextual theological analysis. Historical records show that within approximately fifty years of NZG mission in Tanah Karo, only 5,574 baptisms were recorded, averaging around 500 per year. This statistical pattern reflects not merely missionary inefficiency but the consequences of limited contextualization, especially the rejection of Karo cultural expressions such as the gendang in ecclesial life. The findings demonstrate that authentic evangelism among indigenous societies must be evaluated beyond sacramental metrics and understood as a dialogical, contextual, and culturally embodied process. This study addresses a critical gap in existing scholarship by challenging the 'quantitative evaluation' paradigm that has long dominated the historiography of mission in Tanah Karo. By prioritizing hermeneutical depth over statistical metrics, it provides a novel perspective on the dialectic between faith and indigenous culture, situating baptism as a complex socio-cultural consequence rather than a mere indicator of institutional success.